STUDI KOMPARATIF TAKAFUL DAN ASURANSI KONVENSIONAL - Hardi, Eja Armaz (BISNIS, 2015)
The development of the sect of the sect of the conventionaleconomic science gave birth to two large flows in the economic systemof the countries in the world. The First, the classic economic ideologiesknown with monetary policy in order to maintain the stability of thestate keekonomian. The second, understands the modern economythat focusing the policy of the government in the fiscal sector. In themiddle of the rivalry between two economic ideologies, on the decadeof the 1970s in gagaslah an economic system which is considered as thesolution to accommodate the problems faced by a negra. The Islamiceconomy with the basic philosophy that tend to be outside of themainstream economy offers the principle of values and the purpose ofthe comprehensive and universal.In the economic system countries there financial institutionsBanks and non-bank. In the adjacent is the authormembahasakan one of non-bank financial institutions, namelyinsurance. As in conventional financial institutions there areinsurance, so also on the sharia financial institutions have shariainsurance named with takaful. The subject of done author is gives acomparison between the conventional insurance and takaful. So thatcan provide a description of the opportunities takaful development inIndonesia as a whole.The Annual Report Bappepam-LK 2011 syariah insurance(takaful) number of wealth and investment funds owned by Rp9,2Trillion and Rp7,8 Triliundan growth that occurs on this industryof 31,94% and 33,76%. From this study by relying on the principle thatis owned by the takaful conclusion can be that takaful in Indonesiastill have opportunities that is large enough to perform the expansionof the market by touching the middle to society.